Implementasi Pendekatan User Centered Design Pada Perancangan User Interface dan User Experience Website Worker's - Christofer Veronica Wu; Hasniati; Izmy Alwiah Musdar (STMIK KHARISMA Makassar, 2022)
Abstract: The system quality can be affected by user involvement. It is necessary to implement User Centered Design (UCD) in the UI/UX Design of the Worker's Website. This study aims to evaluate and redesign the UI/UX of Worker's Websites with the UCD and SUS (System Usability Scale) methods in order to make it easier for prospective workers or the public to use website profiling. Data was collected via interview with 30 responds where the results of the interviews are used as a reference for making new designs and then evaluating the new designs with a closed questionnaire to the same respondents. The result of SUS method questionnaire revealed that new design by using UCD was in the excellent category with score 84. It can be concluded that UI/UX design with a UCD allows easy to use worker's website.